Bacteriocins: Potential for Human Health. (12th April 2021) - Huang, Fuqing; Teng, Kunling; Liu, Yayong; Cao, Yanhong; Wang, Tianwei; Ma, Cui; Zhang, Jie; Zhong, Jin
Abstract : Due to the challenges of antibiotic resistance to global health, bacteriocins as antimicrobial compounds have received more and more attention. Bacteriocins are biosynthesized by various microbes and are predominantly used as food preservatives to control foodborne pathogens. Now, increasing researches have focused on bacteriocins as potential clinical antimicrobials or immune-modulating agents to fight against the global threat to human health. Given the broad- or narrow-spectrum antimicrobial activity, bacteriocins have been reported to inhibit a wide range of clinically pathogenic and multidrug-resistant bacteria, thus preventing the infections caused by these bacteria in the human body. Otherwise, some bacteriocins also show anticancer, anti-inflammatory, and immune-modulatory activities. Because of the safety and being not easy to cause drug resistance, some bacteriocins appear to have better efficacy and application prospects than existing therapeutic agents do. In this review, we highlight the potential therapeutic activities of bacteriocins and suggest opportunities for their application.